2018
DOI: 10.1016/j.bpsc.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

When Proactivity Fails: An Electrophysiological Study of Establishing Reference in Schizophrenia

Abstract: These findings suggest that proactive mechanisms of referential processing, reflected by the Nref effect, are impaired in schizophrenia, while reactive mechanisms, reflected by the positivity effects, are relatively spared. Indeed, patients may compensate for proactive deficits by retroactively engaging with context to influence the processing of inputs at a later stage of analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Future work should deepen our insights into this dysfunction in the speech of patients with SZ as compared to that of patients with aphasia and at the neural level. 45 , 46 Such work will provide important targets for future clinical, natural history, and neurobiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should deepen our insights into this dysfunction in the speech of patients with SZ as compared to that of patients with aphasia and at the neural level. 45 , 46 Such work will provide important targets for future clinical, natural history, and neurobiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between linguistic deficits documented here and these other neuropsychological measures are an important desideratum for future work. As of now, the neurocognitive basis of reference has barely been explored (but see [ 73 76 ]), unlike the neurocognitive basis of semantic memory [ 77 79 ]. Our results also bear on the questions of what to look for (and not) in speech output investigated for its predictive or diagnostic role, and of how to design new clinical linguistic tools for the early detection of different forms of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in computational linguistics have suggested considerable potential for language as a biomarker in schizophrenia, as automated linguistic measures can predict symptoms of schizophrenia including FTD (Elvevåg et al 2010;Bedi et al 2015;Holshausen et al 2014). Experimental psycholinguistic studies have also revealed numerous language processing anomalies in schizophrenia, largely in comprehension/perception (Titone et al 2007;Kuperberg 2010;Kuperberg et al 2017; but see Kuperberg et al 2018, for a recent study of semantic priming in a naming task), and in part specific to FTD (Kuperberg et al 1998).…”
Section: Introductionmentioning
confidence: 99%